Perancangan Website UMKM “Majoneko” Sebagai Media PromosiMelalui Aplikasi Blogger - Tarishah Indah Ashira; Rahmawati Zamri; Muhammad Faridz Azizi; Sularno; Novadilastri (CV. ITTC INDONESIA, 2024)
This study seeks to investigate the viral phenomenon of snack foods like mochi and fruit sando within the context of culinary micro, small, and medium enterprises (MSMEs). By conducting case studies and analyzing social media data, this research aims to pinpoint the specific factors contributing to their viral nature, such as innovative flavors, visually appealing presentations, and effective digital marketing tactics. Furthermore, the study delves into the implications of virality on the growth of MSMEs and the evolving snacking habits of consumers.